ANALISIS YURIDIS PELAKSANAAN PROGRAM KEMITRAAN DAN PROGRAM PENDANAAN USAHA MIKRO DAN USAHA KECIL (STUDI Pada: PT TELEKOMUNIKASI INDONESIA (PERSERO) Tbk.): Legal Analysis of the Implementation of Partnership Programs and Funding Programs for Micro and Small Enterprises (Study on: PT Telekomunikasi Indonesia (Persero) Tbk.) - Suffi, Sabrina Nindya; Yunari, Sri Bakti (Faculty of Law, Universitas Trisakti, 2025)
The CSR of State-Owned Enterprises (SOEs) stems from the concept of social responsibility, where social aspects can take the form of Partnership Programs and Micro and Small Business Funding Programs. This includes PT Telekomunikasi Indonesia (Persero) Tbk. Referring to the Regulation of the Minister of SOEs Number PER-02/MBU/7/2017 for the Partnership Program in conjunction with the Regulation of the Minister of SOEs Number 05/MBU/04/2021, both programs represent the CSR pattern of SOEs in contributing to the economic sector, particularly towards community businesses that are still classified as micro and small businesses to increase income. The aim of these partnership and funding programs is to nurture micro and small businesses into more independent and resilient businesses to ensure their sustainability and growth. In practice, of course, the implementation of these two programs encounters several challenges. Using a normative juridical research type, this research is descriptive in nature, based on secondary data consisting of primary, secondary, and tertiary legal materials, and is analyzed qualitatively with deductive conclusions. Based on the analysis results, the implementation of the Partnership Program and the Micro and Small Business Funding Program by PT Telekomunikasi Indonesia (Persero) Tbk has been appropriate, but the distribution of partnerships and fund disbursement is not yet evenly spread and is still concentrated in certain sectors and regions.